EXPERIMENTAL AND CLINICAL OBSERVATIONS AFTER HOMOTRANSPLANTATION OF THE WHOLE LIVER * - STARZL, Thomas E. (1965)
During the past 10 years, much has been learned about homotransplantation of the whole liver using either a replacement (orthotopic) homograft or an auxiliary organ which is inserted at an ectopic site without removal of the recipient’s own liver. The available information concerning these operations has been reviewed from animal experiments, and from the handful of attempts at clinical application.